β-1,3-glucanases expression of Beauveria bassiana in culture with extract of the phytopathogenic Peronospora variabilis and Fusarium oxysporum - Montoya, W. Jhoel (2016)
The fungus Beauveria bassiana Vuill. is well known for its ability entomopathogenic but there is also references to be an antagonist fungus, one of the possible ways of their antagonism it is antibiosis as is known the presence of hydrolytic enzymes in their genome. The main enzymes expressed against phytopathogenic are β-1,3-glucanases, since the cell wall of the phytopathogenic like fungi and oomycetes consists mostly polymers of β-1,3 glucans. The expression of exo-1,3-beta glucanase [XM_008597142.1] and glycoside hydrolase family 55 [XP_008597332.1] genes of B. bassiana was evaluated by qPCR at days 0, 4 and 7, against liquid culture mediums with different carbon sources, 0.1% laminarin, 0.1% pulverized of F. oxysporum and 0.1% pulverized of leaves infested with P. variabilis. Among the genes analyzed the highest rate was found in the cultures with F. oxysporum to the glycoside hydrolase family 55 (GH55) gene, cultures with P. variabilis did not have a significant expression. We postulate that the increased expression of the glycoside hydrolase family 55 (GH55) gene, at day 4, media with F. oxysporum may be important in the metabolism of B. bassiana against this substrate.